Automatic Dependent Surveillance-Broadcast (ADS-B) data observation and quality assessment in Thailand - Waris Ninkaesorn; Sarut Poolgate; Ittipat Lunzear; Somkit Sophan; Watid Phakphisut; Pornchai Supnithi (2021 36th International Technical Conference on Circuits/Systems, Computers and Communications (ITC-CSCC), 2021)
Automatic Dependent Surveillance-Broadcast (ADS-B) technology provides positions and other important parameters for aircraft during phases of flight. As ADS- B technology is required for all aircraft flying in the US as well as Europe, numerous countries are considering the similar adoption. However, its quality will need to be assessed in each region to ascertain the availability. Since King Mongkut's Institute of Technology Ladkrabang (KMITL) is located near the Suvarnabhumi International Airport, an ideal location for ADSB study, in this work, we develop an ADS-B aircraft tracking system using a software receiver on the Raspberry Pi board to obtain the raw ADS-B data and analyze its qualities. Preliminary results show that the Navigation Uncertainty Category position (NUCp) values are in the level 7 at 81.93% of entire messages.
Keywords: Air Traffic Management and Optimization; Advanced Control and Stabilization in Aerospace Systems; UAV Applications and Optimization